Establishment of Aisyiah Stunting Cadres (KSA) with Tuina Massage Expertise in Buluspesantren Sub-district - Siti Mutoharoh; Sumarni; Wulan Rahmadhani; Dyah Puji Astuti (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Nutritional problems can cause stunting in children under five which eventually affects the quality of human resources in Indonesia. Stunting is a growth and development disorder caused by poor nutrition, repeated infections, and inadequate psychosocial stimulation in children. Stunting cases reach 149.2 (22%) million children worldwide and 6.3 million children in Indonesia. Stunting is caused by a lack of knowledge, appetite, and poor feeding behavior. Tuina massage is a complementary therapy to increase appetite. This community service aims to establish Aisyiah Stunting Cadres (KSA) with Tuina massage expertise. KSA assists families with stunted children by providing Tuina massage training for mothers and distributing appetite stimulants. This activity covered 3 stages, namely KSA establishment, training, and family assistance. This involved 20 cadres who meet the criteria of women aged 20-50 years who are physically and mentally healthy. The training materials covered stunting, physical examinations, and Tuina massage. The trained cadres had to assist families and distribute appetite stimulants. This community service managed to establish KSA consisting of 20 cadres. The cadre’s knowledge and skills increased after the training. KSA with insufficient knowledge and skills reduced from 30% to 5%, while KSA with sufficient knowledge and skills reduced from 60% to 30%. KSA With good knowledge and skills increased from 10% to 65%. Around 24 children received appetite stimulants. Conclusion: The establishment of KSA and the provision of appetite stimulants can be an alternative solution to address stunting in children under five.